Venom in verse : Aristophanes in modern Greece - Van Steen, Gonda Aline Hector, 1964- (Princeton, N.J. : Princeton University Press, 2000)
Aristophanes has enjoyed a conspicuous revival in nineteenth- and twentieth-century Greece. Here, Gonda Van Steen provides the first critical analysis of the role of the classical Athenian playwright in modern Greek culture, explaining how the sociopolitical "venom" of Aristophanes' verses remains relevant and appealing to modern Greek audiences. Deriding or challenging well-known figures and conservative values, Aristophanes' comedies transgress authority and continue to speak to many social groups in Greece who have found in him a witty, pointed, and accessible champion from their "native" t
Poisoned gift from antiquity: Aristophanes as Paravase of Koraes' nationalist ideology -- Aristophanes in modern Greek: a demotic, satirical, and theatrical Paravase -- The Lysistrata euphoria of 1900 to 1940: sexual and antifeminist Paravase -- Koun's birds of 1959: Paravase of right-wing politics -- Framing, clowning, and cloning Aristophanes.
Includes bibliographical references (pages 259-273) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Aristophanes -- Appreciation -- Greece; Aristophanes -- Stage history -- Greece; Aristophanes -- Stage history -- Greece; Aristophanes -- Appreciation -- Greece; Aristophane -- Appréciation -- Grèce.; Aristophane -- Histoire scénique -- Grèce.; Aristophanes; Greek drama (Comedy) -- Appreciation -- Greece; Greek drama (Comedy) -- Presentation, Modern; Theater -- Greece -- History; Greek drama (Comedy); Comédie grecque -- Appréciation -- Grèce.; Comédie grecque; Théâtre -- Grèce -- Histoire; DRAMA -- Ancient, Classical & Medieval; Art appreciation; Greek drama (Comedy) -- Appreciation; Greek drama -- Modern presentation; Theater; Greece; Receptie; History